The effects of study-abroad experience to language learning beliefs: A study of Indonesian postgraduate students - Yuwita, Mia (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Study abroad and the effects of it have been a major research topic of language learning beliefs. A wide range of studies has examined the impacts of study abroad on an individual’s language learning beliefs. However, few studies have investigated Indonesian students’ language learning beliefs after studying abroad. This study explores the effects of overseas-study experience to Indonesian postgraduate students’ language learning beliefs at a university in Melbourne, Australia. This current research adopts a qualitative method, specifically semistructured interviews to gain in-depth, rich, and high-quality data. The semi-structured interviews have been conducted with 4 participants (2 males and 2 females). The results of this study demonstrate the impacts of study abroad on students’ language learning beliefs. The participants evidently believed that overseas study affected not only their linguistic skills but also their attitude towards English. They gained experience which could only be drawn from their sojourn period. Thus, this research concludes that the relationship of study-abroad experience and linguistic competencies is sometimes not entirely straightforward. Rather, other aspects may be benefited from overseas study.